DIFFERENTIAL INDICATORS OF SALINITY DIAGNOSTIC EXPRESSION IN DESCRIBING CHANGES IN THE AMOUNT OF SOLUBLE SALTS IN WATER IN THE TERMIZ DISTRICT (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
To date, soil salinization has attracted great interest among scientists as a factor resulting from drastic changes in the environment due to human activity and deterioration of the ecological situation. In this zone, natural and anthropogenic factors have had a strong impact on the geochemical situation and soil formation processes, resulting in a negative water-salt balance and a deterioration in the ecological condition of irrigated soils.